Genetic Analysis of Fasciola Isolates from Buffaloes and Cattle through ITS2 Region Sequencing of rDNA - Qureshi, Asma Waheed; Mansoor, Abu; Mehmood, Sarfraz; Khan, ZaibUllah; Qureshi, Ubaid Ur Rahman (Elite Scientific Publications, 2021)
This study provides the first-time information on internal transcribed spacer 2 (ITS2) gene for genetic characterization of Fasciola isolates from Mardan, Pakistan. No intra and inter specific variation was found among study samples. Sequences comparison of samples were compared with reference sequences selected from different regions of the world which have shown similarity among Fasciola gigantica isolates, however two of reference sequences selected from Egypt and Libya (MT025356 and AB553695, respectively) have shown single nucleotide polymorphism (SNP) at nucleotide position 811 and one Chinese reference sequence JF496709 has shown SNP at nucleotide position 951. Phylogenetic analysis has shown close relationship of our sequence with reference sequences. The possibility of SNP may justify by the fact that geographical locations have impact on genetic variations of Fasciola spp. However, it is recommended that Fasciola spp. from other hosts i.e. goat, sheep, etc. should also be analyzed to develop the genetic profile of Fasciola spp. prevailing in Pakistan. © 2022. Pakistan Journal of Life and Social Sciences. All Rights Reserved.
Keywords: Fasciola; Genetic analysis; Its2; Mardan; Pakistan; Sequencing